Sarcasm and emoticons: Comprehension and emotional impact. Issue 11 (1st November 2016) - Filik, Ruth; Țurcan, Alexandra; Thompson, Dominic; Harvey, Nicole; Davies, Harriet; Turner, Amelia
Abstract : Most theorists agree that sarcasm serves some communicative function that would not be achieved by speaking directly, such as eliciting a particular emotional response in the recipient. One debate concerns whether this kind of language serves to enhance or mute the positive or negative nature of a message. The role of textual devices commonly used to accompany written sarcastic remarks is also unclear. The current research uses a rating task to investigate the influence of textual devices (emoticons and punctuation marks) on the comprehension of, and emotional responses to, sarcastic versus literal criticism and praise, for both unambiguous (Experiment 1) and ambiguous (Experiment 2) materials. Results showed that sarcastic criticism was rated as less negative than literal criticism, and sarcastic praise was rated as less positive than literal praise, suggesting that sarcasm serves to mute the positive or negative nature of the message. In terms of textual devices, results showed that emoticons had a larger influence on both comprehension and emotional impact than punctuation marks.